2016
DOI: 10.1177/1461444816644805
|View full text |Cite
|
Sign up to set email alerts
|

Responsible epistemic technologies: A social-epistemological analysis of autocompleted web search

Abstract: Information providing and gathering increasingly involve technologies like search engines, which actively shape their epistemic surroundings. Yet, a satisfying account of the epistemic responsibilities associated with them does not exist. We analyze automatically generated search suggestions from the perspective of social epistemology to illustrate how epistemic responsibilities associated with a technology can be derived and assigned. Drawing on our previously developed theoretical framework that connects res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…These applications are thus exemplary for our cognitive relation to the Internet. Moreover, these Web applications have received attention from philosophers (Smart 2012;Ludwig 2015;Miller and Record 2017) and so this paper further builds on and is continuous with previous philosophical analyses.…”
Section: The Web As Cognitive Technologymentioning
confidence: 97%
See 1 more Smart Citation
“…These applications are thus exemplary for our cognitive relation to the Internet. Moreover, these Web applications have received attention from philosophers (Smart 2012;Ludwig 2015;Miller and Record 2017) and so this paper further builds on and is continuous with previous philosophical analyses.…”
Section: The Web As Cognitive Technologymentioning
confidence: 97%
“…Page ranking is cognitively and epistemically relevant as empirical research using eye-tracking technology has shown that Webusers implicitly trust Google's ranking in that they prefer to click on links in higher positions even when the abstracts are less relevant to the task they are doing (Pan et al 2007). Another epistemic aspect of Google Search is its autocomplete system (Miller and Record 2017). While typing a query in the search bar, the system suggests two of the user's previous search queries and two popular search queries based on a statistical analysis of other people's search queries in one's geographical location.…”
Section: The Web As Cognitive Technologymentioning
confidence: 99%
“…We conclude by noting that search suggestions via Autocomplete functions, such as the ones we collect for our study, may introduce perceptions about countries that the internet searcher did not previously have or endorse and therefore has the potential to alter their prior national and developmental perceptions. Some have argued that rather than being solely a tool for revealing latent, negative perceptions and biases such as racism and sexism, Google and other autocomplete search utilities are also an integral disseminator of such perceptions (Baker and Potts 2013;Diakopoulos 2015;Miller and Record 2016;Noble 2018). Search algorithms such as Google's autocomplete may contribute to pathological stereotyping of social groups according to nationality by showing users the searches of prior users.…”
Section: Limitationsmentioning
confidence: 99%
“…For this reason, we have an epistemic obligation to ourselves, as knowers, to interact with the online world in an intellectually virtuous way. Miller and Record (2016) distinguish between epistemic responsibility and epistemic practicability. They write:…”
Section: Internet Literacy Skillsmentioning
confidence: 99%
“…The Internet generally provides its users with more epistemic benefits than drawbacks (Heersmink 2016;Smart, Clowes, and Heersmink 2017a); however, unreflexively using Internet-based sources poses epistemic risks for information-seeking and knowledge acquisition. For example, critics point out that search engines may prioritise false or misleading information in search results (Lynch 2016), generate filter bubbles and lead to confirmation bias due to personalised ranking of search results (Simpson 2012;Miller and Record 2013), and sometimes suggest autocompleted search terms that may nudge one towards a wrong path of enquiry (Miller and Record 2016). Also, information on blogs, social media and Internet forums is sometimes posted by anonymous non-experts, which makes it hard to verify the validity of the source.…”
Section: Introductionmentioning
confidence: 99%